Reducing the Electrical Conductivity of ZnO/Ag Nanofiller for Solid Polymer Electrolytes Prepared by Laser Ablation in Polylactic Acid Solution - Permono Adi Putro; Nurfina Yudasari; Yulia Irdawati; Ahmad S. Sulaeman; Akhiruddin Maddu (Jurnal Fisika dan Aplikasinya, 2021)
Solid polymer electrolytes (SPEs) are vital components of fast appearing technology for energy storage-conversion devices. Here, SPEs based on silver (Ag) and zinc oxide (ZnO) nanoparticles are prepared by laser ablation in polylactic acid (PLA) at room temperature. The comparison study of PLA, PLA-ZnO, PLA-ZnO/Ag, and PLA-Ag -based SPEs is conducted in pursuance of the electrical conductivity obtained from electrochemical impedance spectroscopy (EIS) characterization. EIS provides comprehensive analyses, including DCand AC conductivities, dielectric constant, and electrical modulus of the samples. Our results show that PLA-ZnO exhibits an appreciable value of DC conductivity, which insignificantly decreases by Ag existence into PLA-ZnO/Ag. This study suggests that PLA-ZnO remains stable by Ag incorporation; hence, PLA-ZnO/Ag has a great potential as SPEs